Moving Teaching Online: Cultural Barriers Experienced by University Teachers During Covid-19. Issue 1 (8th September 2021) - Littlejohn, Allison; Gourlay, Lesley; Kennedy, Eileen; Logan, Kit; Neumann, Tim; Oliver, Martin; Potter, John; Rode, Jennifer A.
This empirical study examines the experiences of academics and professional service staff in a large UK university during first weeks of the transition to online teaching and working from home during the Covid-19 pandemic. The method draws on the work by Gourlay and Oliver (2018 ) to explore engagement with the digital university in everyday practice. Using data from 412 survey responses and 32 interviews, the study traces varying ways staff characterised themselves during the first months of lockdown in the UK (from March to July, 2020). The findings highlight that university support services underwent a metamorphosis to support the transition to online teaching. However, insufficient attention was paid to the 'identity crisis' and threats perceived by academics who were used to teaching students on campus. Academics tended to focus on transferring traditional teaching practices to the online environment, rather than on changing teaching practice, leaving face-to-face teaching as the default point of reference. These cultural barriers are a persistent obstacle to a more productive engagement with digitalisation. Transitioning to online teaching involves continuing existing work while also learning new practices. Such efforts were challenging for teaching staff who did not have dedicated space at home to work and those with caring responsibilities. This, combined with gendered patterns around caring and the extra support needed by students during the crisis, added emotional labour to already-full workloads. We recommend that intersecting forms of disadvantage be acknowledged, supported and rewarded for universities to create sustainable and just futures.